Occurrence of the sugarcane aphid in sorghum crops in Pernambuco, Brazil - Matheus, Maria L. T.; Matos, Cláudia H. C.; Oliveira, Carlos R. F. de; Nascimento, Astrogilda B. do; Silva, Thieres G. F. da (Entomological Communications, 2025)
The objective of this study was to record the occurrence of the Melanaphis sacchari Zehntner, 1897; Melanaphis sorghi Theobald, 1904 (Hemiptera: Aphididae) complex in sorghum cultivation areas in Serra Talhada, Pernambuco, Brazil. Sorghum samples were collected in the field to identify the specimens. In the laboratory, the specimens were identified, confirming the presence of M. sacchari/M. sorghi. This aphid is a pest that has been spreading in Brazil since 2019, causing significant damage to sorghum. This is the first record of M. sacchari/M. sorghi in Pernambuco, Brazil.